A pH-responsive molecular capsule with an acridine shell: catch and release of large hydrophobic compounds. Issue 8 (12th January 2017) - Kishimoto, Mai; Kondo, Kei; Akita, Munetaka; Yoshizawa, Michito
Abstract : Reversible assembly and disassembly of a supramolecular capsule bearing multiple acridine panels occur in water under neutral and acidic conditions, respectively. The pH-responsive capsule encapsulates various hydrophobic compounds in neutral water and subsequently releases them by simple acidification. Abstract : Unlike common polyaromatic hydrocarbons, acridine is a characteristic compound bearing both π-stackable large surfaces and a protonable nitrogen atom. Here we report the first synthesis of a supramolecular capsule with multiple acridine panels. In water, the assembly and disassembly of the capsule reversibly occur under neutral and acidic conditions, respectively (≥10 cycles). Notably, the pH-responsive capsule encapsulates a variety of large hydrophobic compounds (up to 1.6 nm in diameter) such as coumarins, metallophthalocyanines and subphthalocyanine in neutral water and subsequently releases them by simple addition of acid.